Fermented Cocoa Expansion : From Jembrana to The World - I.B. Komang Surya Werdiyasa (Bali Tourism Board, 2021)
At the beginning of September 2021, Jembrana fermented cocoa product successfully expanded its export market to Japan. In terms of international trade, Indonesia also ranks third with a share of 14.6% of the total 2.96 million tons of world cocoa bean exports in 2010, while the first and second ranks are still occupied by after Côte d'Ivoire and Nigeria with a share of 26 each 7% and 18.6%.3 From the data, Indonesia's role in the world as a cocoa producer is strategic.4 Although known as the third-largest cocoa exporter, before 2013, Indonesian cocoa entrepreneurs were occasionally facing various classic problems. The obstacles were due to poor products and the minor Government support. Currently, With the industrial downstream policies, the cocoa industry's development is heading in a better direction. Further, after being certified by the International certification program, UTZ, Jembrana cocoa product reached a broader market. Jembrana cocoa beans have been known internationally for their unique taste. The fermentation process and post-farm handling become vital in preserving the beans' finest quality.